Cooperative Learning Group Investigation Type of Application Software with Excel and Workbook to Understand The Circle Equation - Awaluddin Awaluddin (Universitas Negeri Malang, 2014)
Pembelajaran Kooperatif Tipe Investigasi Kelompok dengan Penerapan Software Excel dan LKS untuk Memahamkan Persamaan Lingkaran Abstract: This study describes the design and implementation of cooperative learning group investigation with the excel program implementation and student worksheet make learners understand in the material of Circle Equation in class XI IPA 3 RSMABI N1 Kota Batu. Learning implementation process begins with an orientationof students to the problems, teachers organize students to learn and lead in the investigation of individual and group, ended with the presentation of the work and evaluation, as well as reflections. This classroom action research conducted in four meetings and one meeting learning achievement test. Results of this study indicate that a class action, the average percentage of students who pass the study was 88.80% and the lowest value is 76, the average percentage of learners during a learning activity is 84% ​​and can be categorized as active, the average percentage of the activity of the teacher during investigation of cooperative learning groups is 87% and can be considered good. Of the activities of learners are included in the category of active and teacher activities are included in both categories, as well as the learning outcomes of students who are able to achieve mastery learning criteria set out sekurangkurangnya 85% of students scored at least 75, it was concluded that the class action is successful research. Key Words: investigative group, excel software, LKS, Understand Abstrak: Penelitian ini mendeskripsikan rancangan dan pelaksanaan pembelajaran kooperatif tipe investigasi kelompok dengan penerapan program excel dan lembar kerja siswa untuk memahamkan peserta didik pada materi Persamaan Lingkaran dikelas XI IPA 3 RSMABI N1 Kota Batu. Proses pelaksanaan pembelajaran diawali dengan orientasi peserta didik kepada masalah, guru mengorganisasi siswa untuk belajar dan membimbing dalam penyelidikan individual maupun kelompok, diakhiri dengan penyajian hasil karya dan evaluasi, serta refleksi. Penelitian tindakan kelas ini dilakukan dalam empat pertemuan proses pembelajaran dan satu pertemuan tes hasil belajar. Hasil penelitian tindakan kelas ini menunjukkan bahwa, persentase rata-rata peserta didik yang tuntas belajar adalah 88.80% dan nilai terendahnya adalah 76, persentase rata-rata aktivitas peserta didik selama pembelajaran adalah 84% dan dapat dikategorikan aktif, persentase rata-rata aktivitas guru selama pembelajaran kooperatif tipe investigasi kelompok adalah 87% dan dapat dikategorikan baik. Dari aktivitas peserta didik yang termasuk dalam kategori aktif dan aktivitas guru yang termasuk dalam kategori baik, serta hasil belajar peserta didik yang mampu mencapai kriteria ketuntasan belajar yang ditetapkan sekurang-kurangnya 85% siswa mendapat nilai minimal 75, maka disimpulkan bahwa  penelitian tindakan kelas ini berhasil.  Kata kunci: investigasi kelompok, software excel, LKS, memahamkan